Hydrothermal treatment as a means of improving the solubility and enhancing the diaCEST MRI contrast efficiency. (18th July 2022) - Pandey, Shalini; Keerthana, Anil C.; Madhulika, Swati; Prasad, Punit; Peruncheralathan, S.; Ghosh, Arindam
Abstract : Carbon dot formation through the hydrothermal treatment of amino-thioamide improves the diaCEST contrast efficiency. Abstract : As human blood is 90% water, aqueous solubility is key for any drug that is designed for in vivo applications. Good water solubility reduces the dose and makes a drug safer, and exogenous MRI contrast agents are no different. In particular, the efficiency of chemical exchange saturation transfer (CEST)-based MRI contrast agents depends largely on how well they mix with water. Several compounds in spite of containing exchangeable protons do not exhibit CEST contrast due to poor water solubility. In this work, we explore the possibility of carbon quantum dot formation through hydrothermal treatment as a solubility-improvement method for such prospective MRI contrast agents. We report a proof of principle study by demonstrating how a poorly-water-soluble amino-thioamide compound shows a post-treatment improvement in solubility and consequently a several-fold enhancement in the CEST contrast efficiency.